Effect of biochar, cover crops and sewage sludge on soil physical attributes - Vendruscolo, Eduardo Pradi; Alves, Marlene Cristina [UNESP]; Leal, Aguinaldo José Freitas; de Souza, Epitácio José [UNESP]; Souto Filho, Sebastião Nilce (My University, 2018)
Improper soil management culminates in the formation of large areas with reduced life sustaining capacity. The recovery of these areas has high ecological, social and economic importance. The present work was developed with the objective of evaluating the effects of the addition of biochar to treatments previously established 9 years ago for the recovery of an Oxisol. The study design was set in a randomized block design with factorial 6x2, six treatments (T1 – Exposed soil, T2 – Goncalo-alves (Astronium fraxinifolium S.) (GA), T3-Goncalo-alves + Crotalaria júncea L. (GA+CR), T4-Goncalo-alves + Canavalia ensiformis L. (GA+FP); T5-Goncalo-alves and sewage sludge (60 t ha-1) + Urochloa (Syn . Brachiaria) decumbens S. (GA+BR+LE); T6-Native Cerrado Forest) and two periods of soil evaluation, before and after the application of biochar. Soil macroporosity in general, was affected in layers up to 0.10 m, where all treatments, except for GA+CR and GA+BR+LE treatments at a depth of 0.05-0.10 m, showed statistical superiority to the original degraded area when there was the application of biochar. Therefore, in the short term, the application of biochar increases the macroporosity in the surface layer, having little impact in other physical properties of a degraded Oxisol. However, treatments with green manures and sewage sludge resulted in significant improvements in the soil properties studied.
Keywords: Agro-industrial waste; Borrow area; Degraded soil; Organic fertilizer; Oxissol